Conflict Resolution: Comparative Analysis of Separatist Conflicts in Papua, Indonesia, and Zulu, South Africa: Analisis perbandingan Konflik Separatis di Papua, Indonesia dan Zulu, Afrika Selatan - Alhoma Lumban Gaol; Pujo Widodo; Ichsan Malik (CV. AFDIFAL MAJU BERKAH, 2023)
The conflicts in Papua, Indonesia, and Zulu, South Africa, present similarities and differences. This article concentrates on the discussion of the separatist conflict in Papua which is then compared with the separatist conflict in Zulu, South Africa. Which ended with a peace agreement between the Zulu separatist movement and the South African government to take lessons from the Zulu Separatist Conflict to support the resolution of the separatist conflict in Papua, Indonesia. This paper is based on the Library Research methodology and comparative method approach.. There is a big difference, namely that in the Zulu conflict there is a window of opportunity which is the way to peace and ends in a peace agreement. Meanwhile, the Papua conflict does not yet have a window of opportunity which is an opportunity to pave the way for peace. So it is hoped that the Indonesian government will be more observant in seeing opportunities in resolving the Papua conflict. Since the democratic elections, there has been no figure from Papua with an Indonesian nationalist spirit who is able to accommodate and bridge between the Papuan separatist groups and the Government of the Republic of Indonesia. Because looking at the Zulu conflict, apart from the election event there were also nationalist and democratic figures who were black in South Africa.